Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Bokormas Mojokerto Bagian Produksi - Thoriq Nur Fanany (BIMA : Journal of Business and Innovation Management, 2019)
PT. Bokormas Mojokerto is a manufacturing company producing clove cigarettes and filters for the domestic cigarette market. And found a problems about employee performance in the company. The purpose of this research to find out the influence motivation and work dicipline on employee performance in PT. Bokormas Mojokerto production section. The research population was 132 Samples 100 employees with probability techniques especially random sampling. The results of this study indicate that partially motivation has a positive and significant effect on employee performance with thitung 4,326 > ttable. Work discipline partially has a positive and significant effect on employee performancewith thitung 3,982 > ttable 1,66. Simultaneously motivation and work discipline have a positive and significant effect on employe performance. With Fhitung 60,269 > Ftable 2.73 with significance level 0,000. Between the two variables, motivation has a greater influence on employee performance production section PT. Bokormas Mojokerto.